Media Sebagai Etalase Permodelan Karakter Remaja Melalui Program Pencari Bakat pada Televisi Nasional di Indonesia - Faris (ILMU PSIKOLOGI, 2019)
The mass media, no longer appear in a simple form, no longer functions as a tool to help our needs and information only, but has turned into a new land in the economic and industrial fields, all messages are preached, no longer purely just a message without importance, but it has become an interest in itself. Various kinds of information conveyed through television can increase public knowledge of various kinds of existing problems at this time. Television is expected to be able to help the community's need for entertainment, the entertainment world today has a big influence on our society, this is because there are many reality shows on television. This one reality show, that is Indonesian idols are phenomenal. Indonesian idol participant must have a basic talent in the arts, especially in the art of music. Their existence was truly unexpected, in just a few months they have become famous, this event is very powerful so it becomes an entertaining spectacle. The conclusion that can be drawn by the author is, that characters who are informed by reality show programs or talent search programs tend to pushed good proximity factor, because of a sense of friendship and because of desire to be, what can be shown in the talent search program, which is used as a role model or idol on national television in Indonesia.